1997
DOI: 10.1097/00003246-199705000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Transfusing red blood cells stored in citrate phosphate dextrose adenine-1 for 28 days fails to improve tissue oxygenation in rats

Abstract: Storage of rat red blood cells for 28 days in citrate phosphate dextrose adenine-1 impaired their ability to improve tissue oxygenation when transfused into either control or septic rats placed into supply dependency of systemic VO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
14

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(132 citation statements)
references
References 22 publications
2
116
0
14
Order By: Relevance
“…12,17,20,23,24 More importantly in animal and human studies of patients in shock, microvascular perfusion and oxygen consumption remains the same or decreases with RBC transfusion. 8,17,[25][26][27]59 The importance of the effect of RBC storage age on outcomes in critically ill patients is highlighted by the fact that the average age of transfused RBCs in the United States is 22 days 60 and multiple studies have indicated that the age of RBCs transfused is associated with increased morbidity and mortality in the critically ill. 18,22,61 The independent association of the amount of RBC transfusions with decreased survival may be related to the increased storage age of RBCs transfused to all patients in our study (33 days). The mean storage age of RBCs transfused per patient was not able to be analyzed as a variable associated with survival since this data were not recorded per patient.…”
Section: Discussionmentioning
confidence: 99%
“…12,17,20,23,24 More importantly in animal and human studies of patients in shock, microvascular perfusion and oxygen consumption remains the same or decreases with RBC transfusion. 8,17,[25][26][27]59 The importance of the effect of RBC storage age on outcomes in critically ill patients is highlighted by the fact that the average age of transfused RBCs in the United States is 22 days 60 and multiple studies have indicated that the age of RBCs transfused is associated with increased morbidity and mortality in the critically ill. 18,22,61 The independent association of the amount of RBC transfusions with decreased survival may be related to the increased storage age of RBCs transfused to all patients in our study (33 days). The mean storage age of RBCs transfused per patient was not able to be analyzed as a variable associated with survival since this data were not recorded per patient.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced rbc deformability with storage time correlated with decreased rbc survival in vivo (5) and may be accompanied by enhanced lysis of donor rbc with intravascular hemolysis after transfusion. Normal and disease state rodent models have suggested that transfusion of older blood increases senescent rbc clearance (6), iron-induced inflammation (7,8), and tissue oxygen debt due to microcirculatory derangement (9), potentially caused by microcirculatory rbc trapping (10).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have failed to demonstrate benefits of transfusion in septic patients. [91][92][93][94][95] Considering the evidence from above cited studies, septic patients do not benefit from a higher hemoglobin level. The benefits of transfusion are questionable, and the risks are known in this population.…”
Section: Transfusion In Septic Patientsmentioning
confidence: 99%
“…Initially, by day 5 to 10, red cells get spicules on the surface of their membranes. 100 These spicules fall off, and the cells become rounded (spherocytes) but also swell and lose their flexibility. They lose approximately 15% to 20% of their cell membrane phospholipids by day 15 to 28.…”
Section: The Stored Blood Cellmentioning
confidence: 99%
See 1 more Smart Citation